1, 5-Diaminopentane production from xylooligosaccharides using metabolically engineered Corynebacterium glutamicum displaying beta-xylosidase on the cell surface. (December 2017) - Imao, Kenta; Konishi, Rie; Kishida, Mayumi; Hirata, Yuuki; Segawa, Shota; Adachi, Noriko; Matsuura, Rena; Tsuge, Yota; Matsumoto, Takuya; Tanaka, Tsutomu; Kondo, Akihiko
Graphical abstract: Highlights: Metabolically engineered C. glutamicum displays beta-xylosidase . A superior lysine producer was constructed by metabolic engineering. Engineered strains assimilated xylose and xylooligosaccharides. Diaminopentane was produced from xylooligosaccharides. Abstract: Xylooligosaccharide-assimilating Corynebacterium glutamicum strains were constructed using metabolic engineering and cell surface display techniques. First, C. glutamicum was metabolically engineered to create lysine-producing strains. Beta-xylosidase BSU17580 derived from Bacillus subtilis was then expressed on the C. glutamicum cell surface using PorH anchor protein, and enzymes involved in the xylose assimilation pathway were also expressed. Metabolic engineering had no effect on the activity of beta-xylosidase. The engineered strains efficiently consumed xylooligosaccharides and produced 12.4 mM of lysine from 11.9 g/L of xylooligosaccharides as the carbon source. Finally, co-expression of lysine decarboxylase enabled production of 11.6 mM of 1, 5-diaminopentane (cadaverine) from 13 g/L of consumed xylooligosaccharides.